2016
DOI: 10.1039/c5pp00463b
|View full text |Cite
|
Sign up to set email alerts
|

Delivery of a hydrophobic phthalocyanine photosensitizer using PEGylated gold nanoparticle conjugates for the in vivo photodynamic therapy of amelanotic melanoma

Abstract: Photodynamic therapy (PDT) is a treatment of cancer whereby tumours are destroyed by reactive oxygen species generated upon photoactivation of a photosensitizer drug. Hydrophobic photosensitizers are known to be ideal for PDT; however, their hydrophobicity necessitates that they are typically administered using emulsions. Here, a delivery vehicle for photodynamic therapy based on the co-self-assembly of both a Zn(ii)-phthalocyanine derivative photosensitizer and a polyethylene glycol (PEG) derivative onto gold… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
33
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 53 publications
(33 citation statements)
references
References 45 publications
0
33
0
Order By: Relevance
“…[16][17][18][19] PEG has also been used to provide water solubility and to enhance in vivo accumulation in the tumour tissue by the enhanced vascular permeability and retention effect of gold nanoparticles functionalised with a hydrophobic zinc phthalocyanine. 20 Furthermore, PEG can also be a key building block in the synthesis of nanosystems for targeted photodynamic therapy. Cancer cells that overexpress specific cell surface receptors can be selectively recognised by incorporating the corresponding targeting agents such as antibodies or lectins onto the surface of the nanoparticles.…”
Section: Introductionmentioning
confidence: 99%
“…[16][17][18][19] PEG has also been used to provide water solubility and to enhance in vivo accumulation in the tumour tissue by the enhanced vascular permeability and retention effect of gold nanoparticles functionalised with a hydrophobic zinc phthalocyanine. 20 Furthermore, PEG can also be a key building block in the synthesis of nanosystems for targeted photodynamic therapy. Cancer cells that overexpress specific cell surface receptors can be selectively recognised by incorporating the corresponding targeting agents such as antibodies or lectins onto the surface of the nanoparticles.…”
Section: Introductionmentioning
confidence: 99%
“…Gold nano-shells can also be used as photosensitizers in PDT. Due to their capacity to produce major reactive oxygen species for the photo-dynamic technique under NIR light, they consequently proved to suppress the proliferation of melanoma cells [77,78].…”
Section: Photodynamic Therapymentioning
confidence: 99%
“…Photodynamic therapy and electron microscopy studies revealed that the AuNPconjugated C11Pc could result in the reduction of tumour growth and destruction of the tumour vasculature, respectively. In another study by Camerin et al [112], hydrophobic phthalocyanine photosensitizer was conjugated with PEGylated AuNP. This photosensitizer is commonly applied to treatment of melanoma with reactive oxygen species on photodynamic technique.…”
Section: Targeted Therapy Using Gold Nanoparticles In Melanomamentioning
confidence: 99%